New insights into the failure mechanisms of horizontal plate anchors in clay during pull-out. Issue 3 (13th October 2020) - Jalilvand, Soroosh; Gavin, Kenneth; Sivakumar, Vinayagamoothy; Gilbert, Robert B.; Bradshaw, Aaron
Abstract : Offshore wind developments are moving towards deep-water regions where energy is abundant, visual impact is minimised and the larger turbine sizes can make the energy production more cost-effective. One of the key challenges facing the industry is the development of reliable substructures. While fixed foundation systems are widely used for shallow-water (<60 m) developments, permanent anchors are seen as one of the most viable mooring solutions for floating structures in deep water. In the current study, the pull-out behaviour of square plate anchors in clay was investigated using large-displacement finite-element analysis. The anchor capacity and failure mechanism were considered for a range of embedment ratios and undrained shear strengths. Three distinct modes of anchor failure identified in previous studies were examined through the analysis of four descriptors including: the pull-out capacity of the anchor, the pull-out displacement required to mobilise this capacity, the energy absorbed by the anchor during pull-out and the variation of the pull-out capacity with respect to a normalised overburden pressure. The findings of the study are presented in the form of a series of charts that can aid design through understanding of the factors controlling the development of anchor failure modes, in addition to identifying the transition point between different failure mechanisms.